2015
DOI: 10.1515/nor-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Professional autonomy

Abstract: Degree of autonomy is one of the key dimensions of professionalization in journalism. However, the strive for autonomy looks different in different media systems, where pressure on autonomy can come from both political and commercial powers, outside and within the media. Media development also changes the conditions for professional autonomy for journalists, in both a positive and a negative sense. In the comparative research project "Journalism in change", the journalistic cultures in Russia, Poland and Swede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 10 publications
0
2
0
6
Order By: Relevance
“…However, "journalism is still based on real fact and journalistic analysis" (Vartanova, 2010), and the basis of the profession remains its original and essential characteristics associated with the need to promptly provide the audience with important, hard, new, interesting and useful information" (Svitich, 2013). This is also confirmed by the fact that even when evaluating the views of digital journalists about their professional identity, Eldridge and Franklin (2018) distinguish only the move away from traditional hard news to analytical content and "proximity to the audience" postulated by digital journalists themselves, but in the context of media commercialization, the audience is the most significant agent of influence for any category of modern journalists (Anikina, 2012).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, "journalism is still based on real fact and journalistic analysis" (Vartanova, 2010), and the basis of the profession remains its original and essential characteristics associated with the need to promptly provide the audience with important, hard, new, interesting and useful information" (Svitich, 2013). This is also confirmed by the fact that even when evaluating the views of digital journalists about their professional identity, Eldridge and Franklin (2018) distinguish only the move away from traditional hard news to analytical content and "proximity to the audience" postulated by digital journalists themselves, but in the context of media commercialization, the audience is the most significant agent of influence for any category of modern journalists (Anikina, 2012).…”
Section: Introductionmentioning
confidence: 85%
“…This is due to both the negative effects of regular long-term study online (Zinchenko et al, 2019), and the fact that the professional responsibilities of modern journalists still include traditional activities such as information gathering, news production, presentation and design of work, as well as editorial coordination and management. (Anikina, 2012). It has been empirically confirmed that regardless of the influence and extent of digital technologies, working with news and up-to-date information remains the essence of the journalistic profession.…”
Section: Introductionmentioning
confidence: 95%
“…El concepto de autonomía puede ser entendido de tres formas distintas, según Nygren et al (2015). En primer lugar, como un ideal profesional que se intenta alcanzar de manera permanente.…”
Section: Características Estructurales Del Periodismo Freelance: Auto...unclassified
“…On peut distinguer trois niveaux d'autonomie journalistique : l'autonomie symbolique, l'autonomie perçue et l'autonomie factuelle (Nygren et al, 2015).…”
unclassified
“…-L'autonomie perçue des journalistes signifie : ce que disent les journalistes de leur autonomie, comment ils la décrivent. L'autonomie perçue devient manifeste lorsque les journalistes cherchent à s'opposer aux pressions comme la convergence (Singer, 2004), ou l'insistance des sources et du public à intervenir sur les contenus (Deuze, 2005), ou les commandes des propriétaires de média (Nygren et al, 2015). Les journalistes développent ainsi une « rhétorique » à propos de l'autonomie (Charron, 1995), qui les aide à résister aux contraintes, à négocier avec leurs sources et à combattre la censure (Revers, 2014 ;Schlesinger, 1992).…”
unclassified